Tax-Motivated Expense Allocations by Nonprofit Organizations - Yetman, Robert J. (The Accounting Review, 2001)
Although nonprofit organizations are generally exempt from income taxation, they pay taxes on profits from activities unrelated to their primary exempt purpose. Congress intended this tax on unrelated business activities to prevent unfair competition with for-profit businesses and to raise revenue. In the aggregate, nonprofits report annual losses on their taxable activities of more than $1 billion on $4 billion of revenues. In contrast, they report aggregate profits of over $50 billion on their tax-exempt activities. Analysis of a database of confidential tax returns suggests that medical and educational nonprofits allocate expenses from their tax-exempt to their taxable activities to reduce their tax liabilities, although unfortunately it is not possible to determine the extent to which these allocations represent noncompliance with tax laws. In contrast, I find no evidence that charitable nonprofits engage in tax-motivated allocation behavior.